Altered gut microbiota in older adults with mild cognitive impairment: a case-control study - Fan, Kang-Chen; Lin, Chen-Ching; Liu, Yi-Chien; Chao, Yi-Ping; Lai, Yen-Jun; Chiu, Yen-Ling; Chuang, Yi-Fang (Frontiers in Aging Neuroscience, 2023)
Introduction The microbiota-gut-brain axis is implicated in Alzheimer’s disease. Gut microbiota alterations in mild cognitive impairment (MCI) are inconsistent and remain to be understood. This study aims to investigate the gut microbial composition associated with MCI, cognitive functions, and structural brain differences. Methods A nested case-control study was conducted in a community-based prospective cohort where detailed cognitive functions and structural brain images were collected. Thirty-one individuals with MCI were matched to sixty-five cognitively normal controls by age strata, gender, and urban/rural area. Fecal samples were examined using 16S ribosomal RNA (rRNA) V3–V4 sequencing. Compositional differences between the two groups were identified and correlated with the cognitive functions and volumes/thickness of brain structures. Results There was no significant difference in alpha and beta diversity between MCIs and cognitively normal older adults. However, the abundance of the genus Ruminococcus, Butyricimonas, and Oxalobacter decreased in MCI patients, while an increased abundance of nine other genera, such as Flavonifractor, were found in MCIs. Altered genera discriminated MCI patients well from controls (AUC = 84.0%) and were associated with attention and executive function. Conclusion This study provides insights into the role of gut microbiota in the neurodegenerative process.